EFEKTIVITAS PENYELENGGARAAN PEMERINTAHAN KAMPUNG DI DISTRIK SILIMO KABUPATEN YAHUKIMO PROVINSI PAPUA (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACTThis study departs from the phenomenon that the villages in the district governance Silimoindicated Yahukimo Papua Province has not been effective . This condition seems to be related to severalfactors inhibiting . Thus , this study aims to : ( 1 ) To determine the effectiveness of village governance ;and ( 2 ) . To determine the factors inhibiting the achievement of effective governance at the village SilimoDistrict Yahukimo .This study used a qualitative approach to the application of descriptive methods . Data andinformation gathered through interviews with 16 informants techniques , and equipped with observationand documentation , then analyzed by applying descriptive analysis techniques .Based on the analysis of data , it is known that : Implementation of the village administration .Particularly in Silimo District Yahukimo generally not effective . This condition can be seen from thereality of the interview in which the criteria for effectiveness penyelnggaraan village administration hasnot been implemented to the maximum .Thus , it can be concluded that there is some obstacle , namely : low accessibility factors , quantityand quality of human resources village government officials are inadequate , infrastructure andgovernment facilities were inadequate , and still strong patriarchal values that characterize the activity ofthe community , especially government officials village that gave birth to the paternalistic culture asinhibitors of achieving effectiveness village governanceTherefore , it is suggested that regional governments need to reform Yahukimo in several sectors , amongothers : land transportation network , infrastructure , equipment , facilities and budget supporting thedelivery of village governance , improving the quality and quantity of resources and village governmentofficials to build a culture system oriented achievement through religious guidance .Keywords : Effectiveness , Government , Village